PENGARUH PERLAKUAN ALKALI DAN SUSUNAN SERAT TERHADAP WATER ABSORPTION PADA KOMPOSIT HYBRID BERPENGUAT SERAT AGEL TENUN/SERAT GELAS/RESIN POLIESTER - Hestiawan, Hendri; Jamasri, Jamasri; Kusmono, Kusmono (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2019)
The aim of this research is to investigate the effect of alkali treatments and stacking sequences on water absorption in hybrid composites of woven agel fiber/glass fiber/polyester resin. The research materials are woven agel fiber, E-200 glass fiber, unsaturated polyester resin Yukalac 157 BQTN and catalyst of methyl ethyl ketone peroxide (MEKP). The alkali treatment is carried out on the woven agel fibers by soaking the fiber in 5% NaOH solution for 1 hour. Then the fiber is washed with fresh water and dried for 48 hours. Manufacturing techniques used vacuum bagging with a suction pressure of 70 cmHg at room temperature. The amount of reinforcing fiber 7 fibers consists of 3 glass fibers and 4 agel woven fibers. The water absorption test uses a 3.5% NaCl solution for 1080 hours at room temperature. Water absorption test specimens based on ASTM D570 standards. Water absorption test results show that alkali treatment with glass fiber arrangement on the surface effectively holds the entry of water into hybrid composites. This can be seen from the decrease in maximum water absorption (Mm) and diffusion coefficient of hybrid composite, which are 8,67% dan 5,74 x 10-12 m2/s respectively.The aim of this research is to investigate the effect of alkali treatments and stacking sequences on water absorption in hybrid composites of woven agel fiber/glass fiber/polyester resin. The research materials are woven agel fiber, E-200 glass fiber, unsaturated polyester resin Yukalac 157 BQTN and catalyst of methyl ethyl ketone peroxide (MEKP). The alkali treatment is carried out on the woven agel fibers by soaking the fiber in 5% NaOH solution for 1 hour. Then the fiber is washed with fresh water and dried for 48 hours. Manufacturing techniques used vacuum bagging with a suction pressure of 70 cmHg at room temperature. The amount of reinforcing fiber 7 fibers consists of 3 glass fibers and 4 agel woven fibers. The water absorption test uses a 3.5% NaCl solution for 1080 hours at room temperature. Water absorption test specimens based on ASTM D570 standards. Water absorption test results show that alkali treatment with glass fiber arrangement on the surface effectively holds the entry of water into hybrid composites. This can be seen from the decrease in maximum water absorption (Mm) and diffusion coefficient of hybrid composite, which are 8,67% dan 5,74 x 10 -12  m2/s respectively